Grupo Escolar Barnabé - Santos: a presença do método intuitivo no ensino de aritmética na escola primária entre os anos de 1938 a 1948 - Oliveira, Júlio César Santos de (2009)
The present work has for objective to carry through a study of case when analyzing the existing historical documents in the interior of a situated Pertaining to Scholar Group in the city of Santos, whose foundation dates of 1902. Such group, named Pertaining to Barnabé Scholar Group , was the first one in town its building and that is why it still keeps files since its foundation. The study hopes to answer the following question of research: are there concretes elements which can prove the use of the intuitive method by Barnabé Scholar Group, concerning arithmetic teaching? For in such a way, a research on the pedagogical meetings records was carried through, found in the historical archive of the related unit of education. However, only this material would not be enough to answer the question of research. Of this form, also we search information in Yearbooks of the State, published in 1907 and the Teaching Magazines , published between 1902 and 1903. When analyzing the acts, we find information new, as the existence of the Letters of the Parkers, who had been used by the professors, of that unit of education, for the education of Arithmetic. Such material, written for Mr. Francis Wayland Parker, what it seems, possess some elements based on the rules of the intuitive method. Another important fact is the creation of the Scholar Groups from São Paulo, founded by the republicans intending to create a strong school which could cover educational needs, soon after the Republic Proclamation. The theoretical references for this research is based on the works of Le Goff, Bonato, Valente and Dominique Julia. Therefore, these carry through historical research in historical documents and pertaining to school archives. The results gotten for the research show that the presence exists, for some times, indirect, of the intuitive method in the Arithmetic education. We find, in acts, some elements that in took them to believe, that the ideas born with the new method of education, had been in use for a long period